Incidence of anemia in pregnancy and its maternal-fetal outcome in admitted ANC patients in tertiary care center, Bhilai, Chhattisgarh, India - Kanwar, Geetanjali; Prasad, Shweta Rani; Ratnani, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Anemia in pregnancy is an important public health problem in developing countries like India. Anemia results in poor pregnancy outcome and also affects fetal outcome. The present study was conducted to asses maternal and fetal outcome in relation anemia. Aim and objectives of the study was to determine incidence, risk factors and maternal-fetal outcome of anemia in the admitted pregnant women attending obstetrics and gyanecology department, shanakarcharya institute of medical sciences, Bhilai. Methods: This is retrospective observational study conducted among pregnant women admitted in labor room over a period of one year after getting approval from the institutional ethical committee. Results: Out of total 1503 delivery during study period 675 patients were found to be anaemic which gives incidence of 44.5%. Most the pregnant women were moderately anaemic i.e. 50.96% followed by mild (45.04%) and severe (4%) repectively. Among the pregnant women most common type of anaemia is Iron deficiency anaemia (69.65%) followed by Sickle cell anaemia (15.4%). In the present study,90.4% of subject received oral iron, 26.9% received parenteral iron and 19.4% received blood transfusion. Common maternal outcome related to anemia found to be low birth weight (25.2%) followed by premature delivery (22.96%) and fetal outcome in anemic mother in the form of preterm (22.9%) followed by NICU admission (14.37%) and FGR (8.6%). Conclusions: Anemia being one of the most important cause of poor feto maternal outcome should be treated preconceptionaly. There is a need of health education programmes and adequate intake of iron rich diet during pregnancy, to be strengthened for safe maternal and foetal outcomes.